2009
DOI: 10.1074/jbc.m109.054221
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-generating Mitochondrial DNA Mutation Up-regulates Hypoxia-inducible Factor-1α Gene Transcription via Phosphatidylinositol 3-Kinase-Akt/Protein Kinase C/Histone Deacetylase Pathway

Abstract: Lewis lung carcinoma-derived high metastatic A11 cells constitutively overexpress hypoxia-inducible factor (HIF)-1␣ mRNA compared with low metastatic P29 cells. Because A11 cells exclusively possess a G13997A mutation in the mitochondrial NADH dehydrogenase subunit 6 (ND6) gene, we addressed here a causal relationship between the ND6 mutation and the activation of HIF-1␣ transcription, and we investigated the potential mechanism. Using trans-mitochondrial cybrids between A11 and P29 cells, we found that the ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 32 publications
6
88
0
1
Order By: Relevance
“…Most of the transcription factors regulating metabolic events in cancer, including HIF-1α, have a binding site for SP1 in their promoter region (66). HIF-1α expression has been shown to be SP1-dependent in human prostate cancer cells (67), suggesting a crucial regulatory role in cancer metabolism as well as during hypoxia. We showed an upregulation of CEBPα in human GBM cells in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the transcription factors regulating metabolic events in cancer, including HIF-1α, have a binding site for SP1 in their promoter region (66). HIF-1α expression has been shown to be SP1-dependent in human prostate cancer cells (67), suggesting a crucial regulatory role in cancer metabolism as well as during hypoxia. We showed an upregulation of CEBPα in human GBM cells in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis revealed that fusion and fission (p= 0.0472) and mitochondrial localization genes subsets (p=0.0231) were more affected in adenocarcinoma samples. b Relative mtDNA copy number analysis showed a decreased number of mitochondrial genome content in adenocarcinoma when compared to normal colon (p=0.0092) mutated in tumors [39,32], and those mutations were associated with cancer progression mediated by ROS production, PI3K/Akt/PKC pathway activation, and HIF1α [14,13,31,40].…”
Section: Cross-talk Of Mtdna and Nuclear Gene Mutationsmentioning
confidence: 98%
“…ROS induce the release of calcium from intracellular stores resulting in the activation of PKC. The activation of PKC is also required for generating ROS as well as for the ROS-mediated migration of cells [222] and HIF-1a activation [223]. Thus, uncontrolled activation of PKC is a potential mechanism of metal and/or ROS-induced carcinogenesis.…”
Section: Protein Kinasesmentioning
confidence: 98%